2022
DOI: 10.3390/nu14153235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Undernutrition and Obesity on Clinical Outcomes in Adults with Community-Acquired Pneumonia

Abstract: Malnutrition comprises two groups of conditions: undernutrition and overweight or obesity. It has been associated with a high risk of contracting infectious diseases and with elevated mortality rates. Community-acquired pneumonia (CAP) is one of the most common infectious diseases worldwide and its prognosis is affected by a large number of recognizable risk factors. This narrative review updates the information on the impact of malnutrition, including both undernutrition and obesity, on the risk and prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to provide evidence of an "obesity paradox" five years after an acute infectious disease [46]. These findings contribute to previous studies that primarily had short-term follow-up available [19,47,48], as well as to a study of patients with severe sepsis demonstrating survival benefits in obese patients at one year [49].…”
Section: Discussionsupporting
confidence: 64%
“…To the best of our knowledge, this is the first study to provide evidence of an "obesity paradox" five years after an acute infectious disease [46]. These findings contribute to previous studies that primarily had short-term follow-up available [19,47,48], as well as to a study of patients with severe sepsis demonstrating survival benefits in obese patients at one year [49].…”
Section: Discussionsupporting
confidence: 64%
“…This finding is in line with other research on the effects of malnutrition on immune function, acute infection, 34 and the risk of death. 35 The papers reviewed in this study suggested potential mechanisms to explain the relationship between malnutrition and diminished immune function including impairment of gut-barrier function, decreased secretion of protective exocrine substances, decreased levels of plasma complement, atrophy of lymphatic tissues such as the thymus, decreased antibody production in response to vaccination, and cytokine patterns favouring a Th2-response.…”
Section: Malnutrition Is a Risk Factormentioning
confidence: 91%
“…Malnutrition generally implies undernutrition and refers to deviations from adequate and optimal nutritional status [ 9 ]. As a modifiable patient-related risk factor, it is associated with poor outcomes in various diseases [ 10 , 11 ]. To date, several studies have also preliminarily investigated the effects of malnutrition on clinical outcomes following primary TJA, reporting impaired wound healing and greater susceptibility to infection, as well as an increase in other complications [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%